2011
DOI: 10.1186/1471-2180-11-42
|View full text |Cite
|
Sign up to set email alerts
|

Multilocus Variable-Number Tandem-Repeat Analysis, Pulsed-Field Gel Electrophoresis, and Antimicrobial Susceptibility Patterns in Discrimination of Sporadic and Outbreak-Related Strains of Yersinia enterocolitica

Abstract: BackgroundWe assessed the potential of multilocus variable-number tandem-repeat analysis (MLVA), pulsed-field gel electrophoresis (PFGE), and antimicrobial susceptibility testing for discriminating 104 sporadic and outbreak-related Yersinia enterocolitica (YE) bio/serotype 3-4/O:3 and 2/O:9 isolates. MLVA using six VNTR markers was performed in two separate multiplex PCRs, and the fluorescently labeled PCR products were accurately sized on an automated DNA sequencer.ResultsMLVA discriminated 82 sporadic YE 3-4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
63
1
6

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(76 citation statements)
references
References 34 publications
4
63
1
6
Order By: Relevance
“…This intrinsic antibiotic resistance is based on 2 well-known chromosomal betalactamase genes, blaA and blaB (Fàbrega and Vila, 2012). The occurrence of multiresistant human pathogenic Y. enterocolitica strains and a high proportion of antibiotic resistance to chloramphenicol, streptomycin and sulfonamides in porcine strains in Italy have recently been described (Sihvonen et al, 2011b;Bonardi et al, 2014). These findings raise questions about the current situation in Swiss isolates.…”
mentioning
confidence: 70%
See 3 more Smart Citations
“…This intrinsic antibiotic resistance is based on 2 well-known chromosomal betalactamase genes, blaA and blaB (Fàbrega and Vila, 2012). The occurrence of multiresistant human pathogenic Y. enterocolitica strains and a high proportion of antibiotic resistance to chloramphenicol, streptomycin and sulfonamides in porcine strains in Italy have recently been described (Sihvonen et al, 2011b;Bonardi et al, 2014). These findings raise questions about the current situation in Swiss isolates.…”
mentioning
confidence: 70%
“…Recent studies in Europe have reported increasing antibiotic resistance of both human and porcine Y. enterocolitica isolates (Sihvonen et al, 2011b;Bonardi et al, 2014). Low level of antibiotic resistance found in Swiss human strains from 2001-to 2003 underline the increasing tendency in human strains, whereas the rate of acquired antibiotic resistance in recently isolated predominant Swiss porcine Y. enterocolitica BT 4 strains is currently very low.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these, bioserotype 4/O:3 strains have been responsible for yersiniosis cases in Europe, the United States, Canada, and Japan (3)(4)(5)(6). Recently, bioserotype 2/O:9 infections have been on the rise (7)(8)(9). Besides humans, bioserotype 4/O:3 frequently is isolated from samples of pig origin (2,(10)(11)(12)(13).…”
mentioning
confidence: 99%